TINJAUAN YURIDIS TERHADAP HAK PEKERJA YANG TERIKAT DENGAN PERJANJIAN KERJA WAKTU TERTENTU YANG DEMI HUKUM BERUBAH MENJADI PERJANJIAN KERJA WAKTU TIDAK TERTENTU - Z, Grace Elizabeth S; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of which is a form of employment agreement is a time-specific employment agreement. Temporarry Appointment Work Agreement is stipulated in Article 59 of Law Number 13 Year 2003 on Labour. Many companies today are using Temporarry Appointment Work Agreement but many do not comply with the provisions contained in Article 59 of Law Number 13 Year 2003 on Manpower. PT Mekar Usaha Nasional has extended certain time Working Agreement with Moch.Subandi more than once so causing dispute at the time of Moch.Subandi in layoffs. In addition, as happened to the Foundation of Taruna Bakti has also made Temporarry Appointment Work Agreement with Jo Hong Eng not in accordance with the provisions in the Law on Manpower.The purpose of writing this thesis is: First, to know the legal arrangements on the rights of workers in the temporarry appointment work agreement and permanent employment contract; second, to know the temporarry appointment work agreement decision Number: 2 / Pdt.Sus-PHI.G / 2016 /PN.Gsk and Decision Number: 11 / G / 2013 / PHI.BDG with Law Number 3 Year 2003 on Manpower.This type of research is normative legal research or also called doctrinal legal research and this research is descriptive. Sources of data used in this study is secondary data that is data obtained from bibliography such as legal journals, books, judges decision related to research. This data analysis is done qualitatively and deductively deducedFrom the research results of the problem there are two main points that are concluded, Firstly the regulation of workers' rights whether bound in a temporarry appointment work agreement and permanent employment contract is described in an unconscionable manner in Law Number 13 Year 2003 on Manpower. The Second Arrangement of Temporarry Appointment Work Agreement in Law Number 13 Year 2003 Labour does not provide certainty in terms of making a specific employment agreement.Keywords: Worker- Temporarry Appointment Work Agreement - permanent employment contract